Reversible Monolayer-Bilayer Transition in Supported Phospholipid LB Films under the Presence of Water Morphological and Nanomechanical Behavior - Ruiz-Rincón, Silvia (Langmuir : the ACS journal of surfaces and colloids, 2017)
Mixed monolayer Langmuir-Blodgett (LB) films of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and cholesterol (Chol) in the 1:1 ratio have been prepared onto solid mica substrates. Upon immersion in water or in an aqueous HEPES solution (pH 7.4) the monolayer LB films were spontaneously converted into well-organized bilayers leaving free mica areas. The process has been demonstrated to be reversible upon removal of the aqueous solution, resulting in remarkably free of defects monolayers that are homogeneously distributed onto the mica. In addition, the nanomechanical properties exhibited by the as-formed bilayers have been determined by means of AFM breakthrough force studies. The bilayers formed by immersion of the monolayer in an aqueous media exhibit nanomechanical properties and stability under compression analogous to those of DPPC:Chol supported bilayers obtained by other methods previously described in the literature. Consequently, the hydration of a monolayer LB film has been revealed as an easy method to produce well-ordered bilayers that mimic the cell membrane and that could be used as model cell membranes